A Mathematical Model of a Solar Collector Augmented by a Flat Plate above Reflector: Optimum Inclination of Collector and Reflector. (December 2015) - Baccoli, R.; Mastino, C.C.; Innamorati, R.; Serra, L.; Curreli, S.; Ghiani, E.; Ricciu, R.; Marini, M.
Abstract: In this study a theoretical analysis of a collector augmented by a bottom booster reflector is presented. An analytical model has been developed and used to estimate the solar irradiation passing through the transparent cover of a flat collector, both with and without a bottom reflector. The analytical model is based on the anisotropic sky model and takes into account a finite length system with different angular configurations and reciprocal shading and reflections between reflector and collector. Computer simulations have been carried out in order to find the optimum angles of the reflector with respect to the plane of the collector. Optimal inclinations of the collector and reflector for each month at 39° N latitude have been identified.